Geometry of concircular curvature tensor of Kahler manifolds - Rawah A. Zaben; Rana H. Jasim (Tikrit Journal of Pure Science, 2020)
The study deals with the necessary condition where a nearly Kahler manifold of flat concircular tensor has been found. And the relationship between these invariants and additional properties of symmetry concircular tensor, as well as geometrical meaning of the reference in zero of these invariants .